VEILING AND POLITIC IN INDONESIA: PROPAGATING JILBAB IN THE NEW ORDER ERA - Ali Tantowi (PERADA, 2023)
The popularity of Muslim women's clothing in Indonesia for public places takes a very long time and contentious debate. The part of Muslim women's clothing that is often debated is the head covering or veiling. The debate whether the wearing of head coverings for Muslim women is an Islamic obligation or a tradition of the Arab nation in the early twentieth century has shown that Muslim society was seeking an Indonesian Muslim identity. The debate continued in the second phase after Indonesia's independence. Therefore, this article intends to see how the development of the debate occurred and what issues arose and how the Muslim community in general responded. The method used in this paper is the method of content and argument analysis through literature search. Based on this study, it can be concluded that the debate over the use of head coverings in the second period has turned into an issue of Islamic politics where the head covering is used as a symbol of Islamic political struggle which was also influenced by the development of Islamic politics in other Islamic countries.